Criteria for the duration of anti-inflammatory therapy in children with bronchopulmonary dysplasia - Stepanenko Т. І.; Khrystosova, I. M.; Rukavytsia, H. V. (Zaporozhye Medical Journal, 2019)
Objective. To develop criteria for determining the duration of anti-inflammatory therapy and indications for withdrawal of inhaled corticosteroids (ICS) in children with bronchopulmonary dysplasia (BPD). Materials and methods. A total of 56 premature infants with moderate to severe (group 1) and severe (group 2) “classical” bronchopulmonary dysplasia (BPD) who received inhaled budesonide were examined. The groups of children were comparable for gestational age, birth weight and matched for gender. The effectiveness of therapy was evaluated according to the dynamics of clinical manifestations, monitoring of blood oxygen saturation (SаO2) at rest and during exercise, capnographic monitoring and chest radiography changes. Results. Monthly observation of children with BPD during the year showed symptoms resolution in all children in the course of anti-inflammatory ICS therapy (on average within 2.5 months in the children of group 1 and within 4.5 months in the children of group 2), and then the parameters of SаO2 were normalized (on average within 3 and 5.5 months, respectively). Capnographic changes remained longer (from 3 to 12 months). Chest radiographs showed changes within a period from 9 to 12 months and these changes did not always correspond to the symptoms resolution. The conducted factor analysis allowed to identify the criteria for withdrawal of anti-inflammatory therapy. The most significant criteria were the normalization of respiratory rate and reduction in dyspnea, a decrease in SaO2 less than 10 % during exercise, a decrease in unevenness of ventilation-perfusion relations and expiratory time according to Tin/Tex ratio. Changes in the chest radiographs did not have a significant effect on the duration of anti-inflammatory therapy in children with BPD. Conclusions. Thus, the duration of ICS therapy should be individualized taking into account the severity of BPD, the dynamics of clinical manifestations, and the indicators of pulse oximetry at rest and during exercise. Capnography monitoring in children with BPD provides an opportunity to assess objectively the dynamics of bronchial obstruction resolution and to determine the individual terms for withdrawal of ICS. Constant X-ray control is not necessary at the outpatient stage of treatment for children with BPD, as the signs of radiographic recovery are slow and do not influence the choice and duration of anti-inflammatory therapy.